Surplus Labor and Subjectivity in Urban Agriculture: Embodied Work, Contested Work - Drake, Luke (Economic geography, 2019)
This article examines unpaid work within urban agriculture sites. It focuses on the extra work-the surplus labor-that is performed to sustain these sites and how this work relates to subject formation. Land access and subjectivities are widely discussed in the urban agriculture literature, particularly in the Global North, but recent research has also identified the continual supply of labor as a crucial issue as well. However, work dynamics of urban agriculture have seldom been the object of analysis, and little is known about the relationship between unpaid urban agriculture work and subjectivity. I argue that surplus labor is useful for analysis because of the surplus value that is produced through urban agriculture. I draw on the theoretical framework of diverse economies to examine surplus labor through an antiessentialist form of class analysis. A case study from New Jersey, USA, is based on two years of participant observation and forty-eight interviews in twenty cities. The case study reveals how surplus labor is performed, the techniques used to appropriate and distribute surplus labor, the subject formation that occurs through this surplus labor, and models of surplus food distribution that emerge from the juncture of surplus and subjectivity. Conclusions point to contested work practices and the embodied experience of surplus production as keys to subject formation. More broadly, it sheds light on the processes through which surplus labor is performed in unpaid informal forms of enterprise and the role that subject formation plays in that labor.